Condensation heat transfer of R410A on outside of horizontal smooth and three-dimensional enhanced tubes. (February 2019) - Li, Wei; Sun, Zhi-chuan; Guo, Rui-heng; Ma, Xiang; Liu, Zhi-chun; Kukulka, David J.; Ayub, Zahid; Chen, Wei; He, Yan
Abstract: Experimental investigations of flow condensation on the outside surface of one smooth tube and two enhanced surface tubes with the same outer diameter of 12.7 mm were conducted. The refrigerant flowed in an annular space between the test tube and the outer tube. The newly developed 2EHT three-dimensional surfaces have multiple enhancement patterns made up of staggered petal arrays and parallel wavy channels. Tests were performed using refrigerant R410A over a mass flux range of 75–250 kg m − 2  s −1, at average saturation temperatures ranging from 35 to 45  °C. For the smooth tube, the external heat transfer coefficient decreases first and then flattens out gradually at low mass fluxes. Relative significance of inertia force might be the major reason. New prediction correlations for smooth tubes based on the Nusselt's theory were presented, having all data points within ± 4% error band. The effects of saturation temperature, mass flux and vapor quality on heat transfer coefficients for all the tested tubes were analyzed. In addition, the condensation heat transfer coefficient ratio of the 2EHT-2 tube to a smooth tube is only 0.86–0.94 for mass fluxes ranging from 100 to 250 kg m − 2  s −1 . This phenomenon can be explained by the retention of condensate and surface tension effects. New correlations for film condensation in the annular channel outside the 2EHT tubes were also developed, showing a good agreement with experimental data.